Decision making support systems - Mora, Manuel (Idea Group Pub, 2003)
The book presents state of the art knowledge about Decision-Making Support Systems (DMSS). Its main goals are to help diffuse knowledge about effective methods and strategies for successfully designing, developing, implementing, and evaluating decision-making support systems, and to create an awareness among academicians and practitioners about the relevance of decision-making support systems in the current dynamic management environment. Decision-Making Support Systems: Achievements and Challenges for the New Decade is a comprehensive compilation of DMSS thought and vision, dealing with issues such as decision making concepts in organizations